TRANSFORMATIONS OF EXPRESSIVES THROUGH HISTORY IN COGNITIVE-COMMUNICATIVE PERSPECTIVE - Shevchenko, Iryna (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2015)
This article is based on cognitive-communicative approach to discourse in historical pragmatics: it first surveys a variety of different approaches to discourse studies, then takes a close look at the theoretical issues of emotions and finally suggests our understanding of emotional discourse. The article centers on the minimal unit of emotional discourse – a corresponding speech act, with a special emphasis on the historic change of expressives with negative modality, various aspects of these speech acts and their functioning in the English discourse in the 16th - 21st centuries.